1993
DOI: 10.1902/jop.1993.64.3.174
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Studies of Severe Periodontal Disease in an Adolescent Associated With Hypophosphatasia. A Case Report

Abstract: Hypophosphatasia is a congenital disease characterized by defective bone mineralization, deficiency of alkaline phosphatase (ALP) activity, increased excretion of the phosphoethanolamine (PEA) in the urine, and premature loss of the deciduous teeth. A male hypophosphatasia patient (aged 15 years 6 months) with premature exfoliation of the deciduous teeth was referred to our hospital because of severe periodontal destruction in the permanent dentition. Blood and urine tests as well as oral and periodontal exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 21 publications
1
31
0
1
Order By: Relevance
“…Severe periodontitis is uncommon in children 13,14 . It is usually associated with systemic diseases such as hypophosphatasia, 15,16 Papillon‐Lefèvre syndrome, 17,18 Langerhans' cell histiocytosis, 7,8 neutropenia, 19 or leukocyte adhesion deficiency 20 . However, it has also been observed in systemically healthy children 8,14,21‐25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe periodontitis is uncommon in children 13,14 . It is usually associated with systemic diseases such as hypophosphatasia, 15,16 Papillon‐Lefèvre syndrome, 17,18 Langerhans' cell histiocytosis, 7,8 neutropenia, 19 or leukocyte adhesion deficiency 20 . However, it has also been observed in systemically healthy children 8,14,21‐25 .…”
Section: Discussionmentioning
confidence: 99%
“…Other species also likely to be involved included Fusobacterium nucleatum , Eikenella corrodens , and P . gingivalis 8,15,21,22,25 . Among these, A .…”
Section: Discussionmentioning
confidence: 99%
“…Baab et al (1985Baab et al ( , 1986 reported the presence of putative periodontal pathogens in the subgingival microflora and elevated levels of serum antibodies to the periodontal pathogen Porphyromonas gingivalis in HP patients. Watanabe et al (1993) observed a severe periodontal destruction in the permanent dentition associated with serum antibodies to Porphyromonas gingivalis in a subject suffering from HP.…”
Section: Introductionmentioning
confidence: 89%
“…Periodontitis can be viewed as a disturbance of the microbial ecology resulting in an increase in the number of Gram-negative and anaerobic bacteria. Case reports have described an association between HP and periodontitis (Baab et al, , 1986Page and Baab, 1985;Watanabe et al, 1993). Baab et al (1985Baab et al ( , 1986 reported the presence of putative periodontal pathogens in the subgingival microflora and elevated levels of serum antibodies to the periodontal pathogen Porphyromonas gingivalis in HP patients.…”
Section: Introductionmentioning
confidence: 99%
“…Severe destruction of periodontal tissue in young children is mostly associated with systemic diseases such as Papillon-Lefèvre syndrome, hypophosphatasia, neutropenia or histiocytosis X (Shaw and Glenwright 1988;Watanabe et al 1993;Ishikawa et al 1994;Kamma et al 1998;Califano 2003). Only a few reports of aggressive periodontitis cases exist in the literature affecting the primary dentition without evidence of an underlying systemic disease (Suzuki et al 2003;Portaro et al 2008).…”
Section: Discussionmentioning
confidence: 99%